2019
DOI: 10.1111/cup.13412
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of dual 5‐hydroxymethylcytosine/Melan‐A immunohistochemistry in differentiating nodal nevus from metastatic melanoma: An effective first‐line test for the workup of sentinel lymph node specimen

Abstract: Background Distinguishing benign nodal nevus from metastatic melanoma can be diagnostically challenging, with important clinical consequences. Recently, the loss of epigenetic marker, 5‐hydroxymethylcytosine (5‐hmC) expression by immunohistochemistry has been found in melanomas and atypical melanocytic neoplasms. Methods About 41 metastatic melanomas and 20 nodal nevi were retrieved. Nuclear 5‐hmC (brown) and cytoplasmic Melan‐A Red (red) double immunohistochemical staining was performed. Results Total or part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Also, conjunctival melanomas (n = 37) displayed a significant reduction or absence of 5-hmC compared to normal conjunctival nevi (n = 40) (5-hmC expression: 54% vs. 100%, respectively) [24]. To achieve higher diagnostic precision, Siref et al performed a dual 5-hmC/Melan-A immunohistochemical staining in 41 metastatic melanomas and 20 nodal nevi and found a total or partial loss of nuclear expression of 5-hmC in 97.56% of melanomas, while 100% of nodal nevi showed a strong expression [25]. Altogether, 5-hmC is increasingly lost in dysplastic melanocytic nevi and frequently absent in melanomas, which we confirm in our current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Also, conjunctival melanomas (n = 37) displayed a significant reduction or absence of 5-hmC compared to normal conjunctival nevi (n = 40) (5-hmC expression: 54% vs. 100%, respectively) [24]. To achieve higher diagnostic precision, Siref et al performed a dual 5-hmC/Melan-A immunohistochemical staining in 41 metastatic melanomas and 20 nodal nevi and found a total or partial loss of nuclear expression of 5-hmC in 97.56% of melanomas, while 100% of nodal nevi showed a strong expression [25]. Altogether, 5-hmC is increasingly lost in dysplastic melanocytic nevi and frequently absent in melanomas, which we confirm in our current findings.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the function of the biomarkers found in our study. The expression of Melan-AC is highly specific in differentiating lymph nodes from metastatic melanoma ( 22 ), whereas the prognostic function of Melan-AC remains unknown. Syn is abnormally regulated in many cancers and plays an important role in the proliferation and progression of tumor cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published Melan-A positivity rates are considerably discordant for various tumor entities. For example, the fraction of positive tumors varies from 4% to 100% in benign nevi [8][9][10][11][12][13][14][15][16][17][18][19][20], 69%-100% in primary malignant melanoma [8-11, 13, 17, 19-33], 0%-33% in desmoplastic melanoma [8,10,11,17,20,23,31,33], 50%-81% in lymph node metastases of malignant melanoma [13,27], 50%-100% in adrenocortical carcinoma [11,[34][35][36][37][38][39], 68%-100% in adrenocortical adenoma [11,35,37,38], 50%-100% in renal angiomyolipoma [40][41][42][43][44], 0%-20% in leiomyosarcoma [10,11,25], 0%-25% in breast cancer [5,25,35,45], 0%-17% in renal cell carcinoma…”
Section: Melanocyte Antigen (Melanmentioning
confidence: 99%
“…Published Melan‐A positivity rates are considerably discordant for various tumor entities. For example, the fraction of positive tumors varies from 4% to 100% in benign nevi [8–20], 69%–100% in primary malignant melanoma [8–11, 13, 17, 19–33], 0%–33% in desmoplastic melanoma [8, 10, 11, 17, 20, 23, 31, 33], 50%–81% in lymph node metastases of malignant melanoma [13, 27], 50%–100% in adrenocortical carcinoma [11, 34–39], 68%–100% in adrenocortical adenoma [11, 35, 37, 38], 50%–100% in renal angiomyolipoma [40–44], 0%–20% in leiomyosarcoma [10, 11, 25], 0%–25% in breast cancer [5, 25, 35, 45], 0%–17% in renal cell carcinoma [5, 25, 35, 38, 46, 47] and 0%–100% in ovarian carcinomas [5, 35, 48–51]. Variable antibody properties, different staining protocols, and varying criteria for defining positivity may have caused these divergent data.…”
Section: Introductionmentioning
confidence: 99%